Behavior of CFRP-confined Concrete-filled square steel tube columns with section circularized under axial compression. (1st February 2022) - Hu, Zhongjun; Wen, Yuchuan; Wang, Boxin; Li, Xin; Xu, Yan
Highlights: A section circularized method of CFRP-confined CFSST columns was suggested. Parameters that influence the axial compressive properties of columns were analysed. Different combined models were suggested to predict the bearing capacity of columns. Abstract: Eight carbon fiber-reinforced polymer (CFRP)-confined concrete-filled square steel tube (CFSST) specimens and twelve CFRP-confined CFSST specimens with section circularized were tested under axial compression to investigate the effect of different loading conditions and CFRP layers on axial compressive behavior of CFRP-confined CFSST columns with section circularized. Experimental results indicated that section modification method (circularization) improves the CFRP confinement and increases bearing capacity of CFSST columns. Meanwhile, the effect of CFRP layers on the bearing capacity of CFSST columns is also evident. Combination models of Han–Lam & Teng and Mander–Pham & Hadi are suggested in this study for calculating the bearing capacity under different loading conditions. Results showed that predictions are consistent with the experimental results.